RELEVANCE OF COMPETENCIES IN VOCATIONAL HIGH SCHOOL 1 NGAWEN AND COMPETENCE NEEDED IN REAL WORK AND INDUSTRY OF HEAVY EQUIPMENT - Franciscus Asisi Dwi Kristanto; Martubi Martubi (Jurnal Pendidikan Vokasi Otomotif, 2021)
The aims of this study are: (1) to identify the competencies in the curriculum of Heavy Equipment Engineering Vocational High School 1 Ngawen, (2) find out the competencies of labor in industry but not contain in the curriculum of curriculum of Heavy Equipment Engineering Vocational High School 1 Ngawen, and (3) to analyze the compability between competence developed in Heavy Equipment Engineering Vocational High School 1 Ngawen and competence needed in real work and industry engaging in heavy equipment. This study is a descriptive research. The sampling technique uses purposive sampling, with the sample is curriculum of Heavy Equipment Engineering Vocational High School 1 Ngawen and industry engaging in heavy equipment service. The analysis technique used is quantitative descriptive analysis with percentage. The results conclusion is as follows: (1) Competencies developed at curriculum of Heavy Equipment Engineering Vocational High School 1 Ngawen consists of 110 basic competencies, (2) Basic competencies in curriculum of Heavy Equipment Engineering Vocational High School 1 Ngawen all labor in industry heavy equipment service, although form 110 basic competencies there are still five competencies that labor on industry engaging heavy equipment but not applied in the curriculum of Heavy Equipment Engineering Vocational High School 1 Ngawen, (3) The relevance of competence applied in the curriculum of Heavy Equipment Engineering Vocational High School 1 Ngawen of labor in real work and industry results show that 101 basic competencies (91,82%) included very relevant category and 9 basic competencies (8,18%) included relevant category.